Optimization of extraction for efficient recovery of kenaf seed protein isolates: evaluation of physicochemical and techno-functional characteristics - Hamim, Nur Aqilah; Saari, Nazamid; Wan Ibadullah, Wan Zunairah; Mohamed, Abdul Manan Dos; Anwar, Farooq; Hasan, Muhamad Yusuf; Abdul Rahim, Mohd Zulkhairi; Abdul Rahman, Muhammad Sharir; Karim, Roselina (John Wiley and Sons Ltd, 2024)
Background: Kenaf seeds are a rich source of protein; however, finding the best extraction method is crucial to obtaining high-quality protein from these underutilized seeds. This research devised an optimized extraction process for best recovery of kenaf seeds protein using response surface methodology. The key parameters affecting the yield and protein content were optimized, including extraction pH (2–11), seed:water ratio (5:1–50:1), temperature (30–90 °C), and duration (20–360 min). The physicochemical and techno-functional properties of kenaf seed protein isolates (KSPIs) were examined. Results: A maximum protein yield of 12.05 g/100 g with purity level 91.94 g/100 g was obtained using an optimized extraction with pH 11.0, seed:water ratio 50:1, 360 min duration, and temperature 50 °C. The oil and water retention capacities of KSPI were 1.14 mL g−1 and 1.37 mL g−1 respectively. After 30 min at pH 7, KSPIs demonstrated remarkable emulsion capacity (83.12%) and stability (75.63%), along with high foaming capacity (106%) and stability (18.3%). As per high-performance liquid chromatography analysis, arginine, glutamic acid, leucine, phenylalanine, and lysine were the most abundant amino acids detected in KPSIs. The KSPIs’ globular protein structure was successfully verified using analytical approaches, including Fourier transform infrared spectroscopy, protein fraction ratios, and differential scanning calorimetry. Sodium dodecyl sulfate polyacrylamide gel electrophoresis analysis revealed that KPSI has a molecular weight distribution ranging from 10 kDa to 50 kDa. Conclusion: The results of this study support the application of the proposed response-surface-methodology-optimized extraction method for efficient recovery of high-quality kenaf seed proteins that meet the necessary physicochemical and techno-functional requirements.